Introducing Java 17 fundamentals : using Oracle Java SE development kit 17 LTS and OpenJDK 17. (Apress, 2022)
Learn the many new features, enhancements, and updated technologies in the recent long-term support (LTS) release of Java Platform, Standard Edition (Java SE) 17. This video offers an overview of the JDK Release Process, differences between the more frequent non-LTS and the less frequent LTS releases, and various kinds of features such as preview, experimental, incubation and stable. You will understand how to enable and use preview features, as well as the steps to download the latest Java Development Kit (JDK). You'll also gain insight into the deprecation plan of some unused or obsolete APIs which will streamline the future releases of Java SE platform. What You Will Learn Understand what you need to know before upgrading to Java 17 Get familiar with the Java release process Explore the new features and capabilities of Java SE 17 in detail Upgrade to Java SE 17 Enable and Evaluate Preview features of Java SE 17 Who This Video Is For New programmers and software developers, or even some experienced programmers and developers in Java who are new to Java 17.